Web-Based Information System for Transparency in Campus Facility Management - Syafira Nur Fadilla; Siti Sufaidah (NEWTON: Networking and Information Technology, 2026)
The management of campus facilities plays an important role in supporting academic and non-academic activities in higher education institutions. However, facility management processes are often conducted separately and are not fully integrated, resulting in delays in data processing, limited transparency, and difficulties in generating usage reports. This study aims to design and implement a web-based information system to improve transparency and afficiency in campus facility management.the system was developed using the waterfall method, which consists of requirement analysis, system design, implementation, testing, and maintenance stage. Data collection was carried out through interviews, observation, and document analysis related to facility management processes. The resulting system is capable of managing facility data, borrowing and returning processes, maintenance records, reporting features, and master data with role-based access control for administrators. Functional testing was conducted using black-box testing to ensure that all system features operate according to predefined requirements. The results show that the system functions properly and support more structured, transparent, and well-documented facility management processes. The implementation of this system is expected to enhance efficiency, reduce miscommunication, and support decision-making in campus facility management